2018
DOI: 10.1101/287946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional read-through of the long non-coding RNA SVALKA governs plant cold acclimation

Abstract: SummaryMost DNA in the genomes of higher organisms does not encode proteins, but is transcribed by RNA polymerase II (RNAPII) into long non-coding RNA (lncRNA). The biological significance of most lncRNA is largely unclear. Here, we identify a lncRNA (SVALKA) in a cold-sensitive region of the Arabidopsis genome. Mutations in SVALKA affect the timing of maximal CBF1 expression and freezing tolerance. RNAPII read-through transcription of SVALKA results in a cryptic lncRNA overlapping CBF1 on the antisense strand… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Interestingly, the expression of SVALKA is increased after 4 h of cold treatment when CBF1 expression is decreased (Kindgren et al, 2018). RNA Polymerase II read-through transcription of SVALKA results in the production of asCBF1, a cryptic antisense transcript overlapping CBF1 to repress cold-induction of CBF1 gene (Kindgren et al, 2018). This study provides a new regulatory mechanism of CBF1 expression under cold stress.…”
Section: Epigenetic Regulation Of the Cbf-cor Pathwaymentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, the expression of SVALKA is increased after 4 h of cold treatment when CBF1 expression is decreased (Kindgren et al, 2018). RNA Polymerase II read-through transcription of SVALKA results in the production of asCBF1, a cryptic antisense transcript overlapping CBF1 to repress cold-induction of CBF1 gene (Kindgren et al, 2018). This study provides a new regulatory mechanism of CBF1 expression under cold stress.…”
Section: Epigenetic Regulation Of the Cbf-cor Pathwaymentioning
confidence: 80%
“…A recent study reported a cold-responsive long noncoding RNA, named SVALKA, plays a role in regulating CBF1 expression. Interestingly, the expression of SVALKA is increased after 4 h of cold treatment when CBF1 expression is decreased (Kindgren et al, 2018). RNA Polymerase II read-through transcription of SVALKA results in the production of asCBF1, a cryptic antisense transcript overlapping CBF1 to repress cold-induction of CBF1 gene (Kindgren et al, 2018).…”
Section: Epigenetic Regulation Of the Cbf-cor Pathwaymentioning
confidence: 99%
“…stands for not significant. E Image of homozygous mutant nrpb2-2 fully complemented by NRPB2 WT -FLAG (top, NRPB2 WT +/+ nrpb2-2 À/À ) and partially complemented by NRPB2 Y732F -FLAG (bottom, immunoprecipitation from plants (RNAPII-ChIP) [25,37], we analyzed nascent RNA attached to RNAPII to monitor RNAPII elongation [38]. We identified three pathogen resistance-related Toll/interleukin receptor (TIR)-type NB-LRR genes AT4G19520, AT5G41740, and AT5G41750 [39,40] that are rapidly induced by flagellin 22 treatment.…”
Section: Nrpb2 Y732f Accelerates Rnapii Transcription In Vivomentioning
confidence: 99%
“…We identified three pathogen resistance-related Toll/interleukin receptor (TIR)-type NB-LRR genes AT4G19520, AT5G41740, and AT5G41750 [39,40] that are rapidly induced by flagellin 22 treatment. To monitor the "waves" of RNAPII elongation on these three genes after transcriptional induction, we performed a time course experiment during flagellin 22 treatment and determined the RNAPII signal by analyzing nascent RNA attached to RNAPII [38]. We chose NRPB2 WT -FLAG +/+ Col-0 and NRPB2 Y732F -FLAG +/+ Col-0 as material for this assay since we detected no differences in growth and immune response in this background.…”
Section: Nrpb2 Y732f Accelerates Rnapii Transcription In Vivomentioning
confidence: 99%
See 1 more Smart Citation